Fabrication and mechanical properties of flaxseed fiber bundle-reinforced polybutylene succinate composites. (July 2020) - Azhar, Sayed Waqar; Xu, Fujun; Zhang, Yinnan; Qiu, Yiping
Flaxseed plants are widely grown globally due to the beneficial seed oil derivatives for human and animal consumption and other industrial uses. However, plentiful flaxseed straws are annually burnt after the harvesting of seeds, lacking utilization of the abundant flaxseed fibers, resulting in wastage of a valuable fiber resource and drastic increase in environmental pollution. In this study, initially the chemical composition and mechanical property of flaxseed fiber bundle were investigated, which resulted as 40.11% cellulose, 28.27% hemi-cellulose, 15.08% lignin, 6.3% pectin, 3.1% wax, and the tensile strength of 1.14 cN/dTex. The surface modification treatment was carried out with concentrations of 10 g/L and 20 g/L sodium hydroxide (NaOH). Later, flaxseed fiber bundles reinforced Polybutylene Succinate (PBS) resin composites were fabricated by thermal compression method. The tensile strength of untreated flaxseed fiber bundle/PBS composites was 78.2 MPa, while the flexural strength of 20 g/L NaOH treated flaxseed fiber bundle/PBS composites showed 84% increment from 26.70 MPa to 49.16 MPa. The scanning electron microscopy (SEM) images revealed significantly rougher surface morphology and stronger interfacial bonding of the alkali treated fiber bundles with matrix. The good mechanical properties observed demonstrated the absolute potential of resultant composites reinforced by flaxseed fiber bundles for utilization in the civil and industrial applications.